The challenges oh 1 Malaysia and the reality of youth's involvement with the unity campaign on television. - Dahalan, Dzulhailmi; Ahmad, Nobaya; Hassan, Md. Salleh; Muda, Mariah; Othman, Jamilah; Ahmad, Nor Azliza Wanis (INSInet Publication, 2011)
Today’s youth are the ones who are exposed to the development of ICT. Therefore, the print and electronic media are the main communicators as sources of information for youths. The question is, how do these sources of information use these channels for the benefit of youth’s education? This article is the discussion about the challenges to realize the succession of 1Malaysia based on the research founding by Nobaya et al., (2008) related to youth’s involvement with the unity campaign being shown through television channels. The discussion about the succession of 1Malaysia in relation to the youth generation is an issue that should be given serious attention by all in tandem with the realization that this generation is the back up for the current nation’s leaders who will determine the stability and the continuation of a harmonious ethnic relationship in a multi racial society for the nation’s future. The question whether they understand or not the real meaning in developing 1Malaysia has to be critically analyzed and discussed. Even though the basic research data by Nobaya et al. (2008) did not directly measure youth’s understanding about the succession of 1Malaysia but this research will measure the level of youth’s involvement with the unity campaign shown through Malaysian television channels, which will reflect the 1Malaysia practice level nowadays within the youth’s generation in the aspect of unity. The findings show Malaysia’s youth understand and embrace the unity campaign being aired but lack in performing the behavior that could spurt unity’s growth. The discussion in this article is hoped to shape the thinking of all parties in enriching the succession of 1Malaysia which is fundamentally based on unity’s practice in a multi cultural society especially in the youth’s generation.